Ultrastructural observations on the development of Ceratomyxa aegyptiaca (Myxozoa: Bivalvulida) infecting Solea aegyptiaca (Pleuronectiformes: Soleidae) from Tunisian coastal lagoon - Yemmen, Chiraz; Quilichini, Yann; Marchand, Bernard; Bahri, Sihem (Zootaxa, 2016)
Ultrastructural description of Ceratomyxa aegyptiaca Yemmen, Marton, Eszterbauer and Bahri, 2012 infecting the gallbladder of Solea aegyptiaca Chabanaud, 1927 from a tunisian north-east costal lagoon, was presented in this study. The primary cell was attached to the gallbladder epithelium and presented at one side cytoplasmic projections corresponding to pinocytotic invaginations. Netherless, early sporogonic stages development was carried with contact to the epithelial cells of gallbladder. Immature spores were identified in early sporoblasts by their valvogenic, capsulogenic and binucleated sporoplasmic cells. Capsulogenesis was asynchronous. Each capsulogenic cell presented a large condensed nucleus and a capsular primordium that extended into an external tube. The eversion and coiling of the external tube gave rise to the polar filament, which displayed six turns and an apical plug.